Maqāṣid Al-Syarī‘Ah (Tujuan Disyariatkannya Hukum Islam) Dan Aplikasinya Dalam Pemikiran Fiqh Para Ahli Fiqh - Izza Rayyan; Zebada Darell Frijatuluah (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Maqāṣid al-syarī‘ah is a fundamental concept in Islamic law that emphasizes that every legal provision aims to achieve human welfare. This article aims to analyze the concept of maqāṣid al-syarī‘ah and its application in Islamic jurisprudence (fiqh), particularly in responding to contemporary social, economic, and humanitarian challenges. This study employs a qualitative approach using library research, drawing data from the Qur’an, hadith, classical and contemporary Islamic scholars’ works, and relevant academic journals. The data are analyzed using a descriptive-analytical method to explore the development of maqāṣid theory and its implications for the dynamics of Islamic law. The findings indicate that maqāṣid al-syarī‘ah, through its classification into ḍarūriyyāt, ḥājiyyāt, and taḥsīniyyāt, serves as a crucial foundation for protecting the five essential values: religion, life, intellect, lineage, and property. The maqāṣid-based approach enables fiqh to be more flexible, contextual, and adaptive while remaining grounded in Islamic legal principles. Therefore, maqāṣid al-syarī‘ah plays a strategic role in ensuring that Islamic law remains relevant, responsive, and just in the modern era.